Importens påverkan på Etiopiens jordbruk - Björk, Linnéa (2005)
Trade is important for every country in the world. Commodities are transported between rich and poor countries everyday. Some of the trading partners are EU and Ethiopia, this because of less expensive commodities from EU than they are in Ethiopia. The most important agricultural commodity is wheat. Ethiopia is a poor country, whose inhabitants mostly are living on agriculture. The majority of the people are living from agricultural production and because of that changes in the price of wheat affect many people in the country. Using economic theory, this thesis investigates if and if possible how, Ethiopia is influenced from the import. Welfare theory complemented with analysis and discussions were used while answering the question. To investigate the effects in Ethiopia two different price changes were studied. Because of problems finding good data the thesis only cover the years 1999 to 2003. The thesis is ending with a discussion around the results and things that could influence the results. The result shows that a lower price influence gives a lower net welfare, but there is a winning situation if there is trade with EU. But it is hard to se if there is a winning situation for every one in Ethiopia. Probably there is a loss for the farmers because they get less money when they compete with commodities from EU.